Professional trajectory of postgraduate egress in Dentistry in Brazil: a literature review (Research, Society and Development, 2020)
Introduction: Many career perspectives are available within the dental sciences and with the continued growth and consolidation of postgraduate in Brazil these perspectives are even greater. Objectives: This article aims to review the current literature on the professional trajectory of masters and PhDs egress from brazilian postgraduate in dentistry. Methodology: A search was carried out on the most prestigious indexing bases within the CAPES assessment, which is currently Scopus, Web of Sciences and Google Scholar. Only 5 articles were within the scope of this research and were eligible to compose this review. Conclusion: The current medical literature is very poor in terms of the professional trajectory of masters and PhDs egress from Brazilian postgraduate studies in dentistry. Other studies must be carried out so that there is a more reliable parameter for collection and comparison between different studies and only in this way can a more consistent conclusion on this topic be established.